Influence of lithium flouride additive on polyethersulfone membranes - Idris, Ani; Ahmed, Iqbal; Nihal Ah., Ansari Akhlaque Ah.; Mohd Noor, Nur Diana (2007)
The objective of this research is to investigate the influence of the additive lithium fluoride anhydrous (LiF) concentration on the performance of polyethersulfone (PES) membrane. Various concentration of LiF has been mixed with PES in the range of 1-5% . This distinctive series of dope formulations of PES and LiF was prepared using N,N-dimethylformamide (DMF) as solvent. Viscosities of the dope solution were measured and the performances of the PES membranes were evaluated in terms of polyethylene glycol (PEG) separation and its molecular weight cut off (MWCO) is determined. The results indicated that the additive LiF showed significant effect in reducing viscosity of dope solution by 2.5-5 times. Its presence has improved both the permeation and solute rejection rate with the best concentration kept to less than 3% by weight. Dope solutions containing 1%-3% were discovered to have highest rejection rate with MWCO at approximately 8.1 kDa, 7.1 kDa and 8.45 kDa respectively with reasonably flux rates.